Significance of HbA(1c) and its measurement in the diagnosis of diabetes mellitus: US experience - Juarez, Deborah Taira (Dove Medical Press, 2014)
The 2014 American Diabetes Association guidelines denote four means of diagnosing diabetes. The first of these is a glycosylated hemoglobin (HbA(1c)) >6.5%. This literature review summarizes studies (n=47) in the USA examining the significance, strengths, and limitations of using HbA(1c) as a diagnostic tool for diabetes, relative to other available means. Due to the relatively recent adoption of HbA(1c) as a diabetes mellitus diagnostic tool, a hybrid systematic, truncated review of the literature was implemented. Based on these studies, we conclude that HbA(1c) screening for diabetes has been found to be convenient and effective in diagnosing diabetes. HbA(1c) screening is particularly helpful in community-based and acute care settings where tests requiring fasting are not practical. Using HbA(1c) to diagnose diabetes also has some limitations. For instance, HbA(1c) testing may underestimate the prevalence of diabetes, particularly among whites. Because this bias differs by racial group, prevalence and resulting estimates of health disparities based on HbA(1c) screening differ from those based on other methods of diagnosis. In addition, existing evidence suggests that HbA(1c) screening may not be valid in certain subgroups, such as children, women with gestational diabetes, patients with human immunodeficiency virus, and those with prediabetes. Further guidelines are needed to clarify the appropriate use of HbA(1c) screening in these populations.